Principal's Leadership Strategy In Overcoming The Influence Of Social Media On Students - Suryati, Suryati (Universitas Pakuan, 2022)
The presence of social media as a logical consequence of the sophistication of technological developments is a big challenge for the world of education. The impact of social media is not only positive but also harmful and affects school-age children, so an active role is needed from all parties in education, especially school principals, to be able to make social media an opportunity and at the same time demand the ability to take advantage of social media as an opportunity. However, apart from the positive influence that exists, some things are a weakness of social media, namely not being able to transform students' character as social media users. This research is qualitative descriptive research by conducting a literature study. This study identifies articles and journals related to school principals' leadership in tackling the influence of social media on students. Data collection methods accompany this research through literature study by collecting data through articles and journals, analyzing data, and finally drawing conclusions about the problems studied. Moreover, the findings of this study indicate that the principal has a strategic role in achieving the success of an educational process. The existence of social media can be seen as a challenge and opportunity for all school members through the development of a social learning leadership model.